Variation in resistance to isometamidium chloride and diminazene aceturate by clones derived from a stock of Trypanosoma congolense - Peregrine, A.S.; Knowles, G.; Ibitayo, A.I.; Scott, J.R.; Moloo, S.K.; Murphy, N.B. (Cambridge University Press, 1991)
Nine clones were derived from a drug-resistantTrypanosoma congolensestock (IL 2856) and characterized in mice for their sensitivity to isometamidium chloride and diminazene aceturate. All clones were derived from the stock without drug selection and expressed high levels of resistance to isometamidium chloride (50% curative dose [CD50] values ranging from 1·5 to 5·1 mg/kg) and intermediate to high levels of resistance to diminazene aceturate (CD50values ranging from 5·1 to 21·0 mg/kg). By contrast, the isometamidium chloride and diminazene aceturate CD50values for a drug-sensitive clone,T. congolenseIL 1180, were 0·018 mg/kg and 2·3 mg/kg, respectively. For both drugs, there appeared to be significantly different levels in expression of drug resistance amongst the 9 clones derived from IL 2856. Isoenzyme analysis of 7 enzymes showed that all 9 clones expressed the same electrophoretic variants. Thus, all 9 clones were identical for these phenotypic markers. The clone which expressed the highest level of resistance to isometamidium in mice (IL 3270) was transmitted to Boran cattle via the bite of infectedGlossina morsitans centralis. IL 3270 produced an infection rate in tsetse of 5·0%. The resulting infections in cattle were shown to be resistant to intramuscular treatment with 2·0 mg/kg isometamidium chloride and 14·0 mg/kg diminazene aceturate. This contrasts with doses of 0·25 mg/kg isometamidium chloride or 3·5 mg/kg diminazene aceturate which are deemed sufficient to cure fully sensitive infections. Finally, 9 clones (subclones) were derived from IL 3270 and characterized in mice for their sensitivity to isometamidium chloride. Seven of the subclones expressed a significantly lower level of resistance to isometamidium than the parental clone and amongst the subclones there was significant variation in resistance. Thus, expression of a high level of resistance to isometamidium appears to be unstable in the rodent host and at least a component of the genetic determinant(s) for this drug-resistant phenotype is (are) likely to be unstable.